Stylistic and psychological analysis of Rudyard Kipling’s “Just So Stories” - Galstyan, Armenuhi (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
The subject matter of the present paper is the linguo - stylistic and psychological analysis of Rudyard Kipling’s “Just So Stories” as emotional means to motivate children to study English as a foreign language.“Just So Stories” are tales for children, where the author tells how the world, surrounding the child, was created, why everything in this world is “just so”, answers the questions that children like to ask so much: “what and why and when and how and where and who?” For children, who are not adapted to studying, and who achieve information with the help of games, fairy tales in general and Kipling’s “Just so stories” in particular serve as a ground for not only developing the intellect, sense of humor and imagination of children, but also take away all boundaries in perceiving information in a foreign language and enhance interest towards the origin of familiar and unusual things.  The knowledge, contained in tales is inmost and conveys great information about animals, people, the world they live in and the interrelation of everything in life.Fairy tales develop not only the imagination of children but also establish some kind of bridge between the fantasy and the real life. Fairy tale reading attracts children, increases the motivation of learning a foreign language. Tale has an impact on children’s emotional state: it reduces anxiety, fear and confusion and gives food for perception, empathy and communication with favorite heroes, creates a fairy atmosphere full of enthusiasm and joy.The importance of the fact that all "just so stories" end with a poem cannot be underestimated. Firstly, poems and chants are short, emotionally colored and easy to remember. Secondly, poetic texts are great materials for practicing rhythm, intonation of a foreign speech and for improving the pronunciation. And thirdly, multiple repetitions of foreign words and word combinations with the help of poems do not seem artificial. Accordingly, the use of poetry contributes to the development of different language skills, like reading, listening and speaking.